Public perceptions of the role of Australian pharmacists in cardiovascular disease - Peterson, G.; Jackson, S.; Hughes, Jeffery; Fitzmaurice, K.; Murphy, L. (Blackwell Science, 2010)
Background and Objective: To assess the public's perception of pharmacists' involvement and role in cardiovascular disease prevention and management. Methods: A computer-assisted telephone interviewof 505 households was conducted. The survey was administered to metropolitan, rural and remote residents over the age of 30 years. The interview had questions on the patient's general satisfaction with the quality of service provided by their regular community pharmacy, including factors such as location, professionalism, prices, product range and knowledge of the staff. The participants were asked if they thought pharmacists were capable of providing screening, testing and drug prescribing services for blood pressure and cholesterol, and how likely they would be to use these services through a pharmacy. The interview also included questions on how likely this person would be to seek advice on lifestyle changes and medications from various health professionals, including pharmacists.Results: The majority (97%) were satisfied with the service provided at their regular pharmacy. Those surveyed agreed or strongly agreed that pharmacists are capable of providing screening or testing for raised blood pressure (52%) and diabetes (51%), with a minority (38%) agreeing that pharmacists are capable of testing for raised cholesterol. The pharmacist's role with perceived highest capability by those surveyed was in providing advice on how to take medicines properly, with 90% of respondents willing to seek this advice from their pharmacist. A limited role by pharmacists was seen in the diagnosis of CVD and prescribing medications. In relation to the prevention of CVD, even though 76% of respondents believed that pharmacists are capable of providing advice on lifestyle changes (e.g. weight loss, smoking and alcohol intake), only 8% of current or past smokers had sought assistance to give up smoking at their pharmacy and while 69% of all respondents had sought help with weight control, only 3% of these had looked towards their pharmacy for assistance. Conclusion: There was belief by those Australians surveyed that community pharmacists are capable of providing screening for hypertensionand diabetes. Through these services and in conjunction with counselling on CVD risk reduction, pharmacists may play an important role in the reduction of CVD, ultimately improving public health and decreasing the burden on Australia's health care system. However, at present pharmacists are not being fully utilized to deliver health promotion advice and contribute to the prevention of CVD.